The Prevalence of overweight nurses in Italy: a systematic review - Antonio Brusini; Simone Tersigni; Danilo Curatolo; Mattia Giacomuzzi Trepiccione; Benedetta Papotti (Infermieristica Journal, 2024)
Introduction: A nurse is a healthcare professional who deals with health in an increasingly older world, and it is essential to maintain a healthy lifestyle. The aim of this study was to estimate the prevalence of overweight nurses and make a comparison with the general population. Methods: A systematic review was performed on PubMed, Web of Science, Scopus, and Cinahl Plus; only primary studies conducted in Italy were considered, starting from 01/01/2013. Results: The range of nurses with BMI ≥ 25 ranged from 29.6% to over 62%. Shi work, especially night shi s, is a risk factor for incurring a BMI ≥ 25. Conclusions: It is important to seek a policy of reducing the BMI among nurses, as the nursing population faces the risk of incurring overweight and obesity conditions, even if in smaller terms than the general population.